PENGARUH MEDIA ZEP TERHADAP HASIL BELAJAR SISWA KELAS IV MATERI PENERAPAN NILAI PANCASILA SDN SOOCAH 2 - Naila Arrafa; Dinda Marta Rudistya; Dhea Ayu Tryas Febrianty; Ika Dian Rahmawati (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2026)
This research is motivated by the low learning outcomes of fourth-grade students on the application of Pancasila values ​​​​material due to teacher-centered learning and the lack of use of interactive learning media. This study aims to determine the effect of the use of ZEP-based media on the learning outcomes of fourth-grade students on the application of Pancasila values ​​​​material at SDN Socah 2 Bangkalan. The study used a quantitative approach with a One Group Pre-test and Post-test Design. The research subjects were 20 fourth-grade students who were determined using saturated sampling techniques. Data collection techniques included tests, observations, and documentation. Data analysis was carried out descriptively and inferentially using paired sample t-tests with the help of SPSS. The results showed an increase in learning outcomes after the use of ZEP-based media. Students' pre-test scores were in the range of 20–60, while post-test scores increased to 60–100. The results of the paired sample t-test showed a mean difference of -40.000, a calculated t-value of -27.568, and a significance value (Sig. 2-tailed) of 0.000 < 0.05. These results indicate a significant difference between the pre-test and post-test scores. Furthermore, observations indicated that students were more active, enthusiastic, and engaged during the learning process. The results of the study demonstrate that ZEP-based media significantly influenced the learning outcomes of fourth-grade students in the application of Pancasila values ​​at SDN Socah 2 Bangkalan and can be used as an alternative learning medium that is innovative, interactive, and in line with technological developments in elementary school .